Privacy and user awareness on Facebook - Nyoni, Phillip; Velempini, Mthulisi (South African Journal of Science, 2018)
Users’ privacy on social media platforms continues to be important as users face numerous threats to their personal data. Social media sites such as Facebook store large amounts of users’ personal data which make such sites prime targets for hackers. Research has shown that users have been subjected to privacy attacks in which hacked personal data are sold to online marketers. These incidents have prompted the need to protect users’ privacy against data theft by third parties. We investigated the privacy risks that social media users on Facebook face when online. The privacy awareness of regular users of Facebook was evaluated through the observation of their online activities. Facebook was selected as a case study because it is the largest and most popular social media platform in South Africa. A sample group of Facebook users was selected for this study based on their activeness (or frequency of posting,uploaded or liking) on the site. Findings indicate that users’ personal data can be obtained as they are publicly available on Facebook. The implication of this finding is that users lack adequate awareness on protection tools designed to protect their personal data, and as a result, they risk losing their data and privacy. Significance: • This study serves as an assessment tool for the privacy and security features of the social media siteFacebook. This assessment tool can help users of social media sites to evaluate their own behaviour and usage patterns on Facebook. It can also assist social media site designers in considering the effectiveness of current measures, which are designed to ensure that the privacy and safety of users are protected.
Article published in the South African Journal of Science;Volume 114 | Number 5/6
Keywords: Social networks; Personal data; Online profiling; Third-party applications; Online advertising; Online social networks; Confidential communication